KESALEHAN LINGKUNGAN DAN KESEHATAN MASYARAKAT KAMPUS - Khalid Rahman; Albar Adetary Hasibuan (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
The health of the campus community is very much determined by each individual for doing, learning, and working. In the campus environment for studying and working which is thought to cause occupational diseases, so three main steps are taken, such as identification, evaluation and control of various occupational hazards and risks. This also occurs for students studying in a campus environment related to the pre-test of student conditions, the learning process, evaluation of learning outcomes and control for learning outcomes such as thought, psychic and physical. This paper aims to describe (a) What is the most influential variable for determining the health level in the campus community, and (b) Is there a relationship between the environmental godliness and the campus public health. The research is quantitative-descriptive. The research method used is a descriptive-explorative with survey. The research data was obtained through a questionnaire adjusted to indicators for measuring the health in the campus community, such as: utilization of time and balancing of life, rational thinking, physical and mental health, and social solidarity. Then the data are validated and analyzed to examine the relationship between independent variable (X) that is the environmental godliness with dependent variable (Y) that is the campus public health. Then further more this research also wants to examine relationship between the godliness sub-variables and the health sub-variables are being indicators. The results of this study have a significant relationship between environmental godliness and the campus public health in Malang. There is a strong influence of environmental godliness on the campus public health in Malang, both physically, mentally, mindly and spiritually.